Hubungan Tingkat Kecukupan Energi dan Zat Gizi Makro dengan Status Gizi Santri Pondok Pesantren Salafiyah Al-Amin Sleman - Fazri Adi Saputra; Endri Yuliati; Siti Wahyuningsih (Jurnal Kesehatan Indonesia, 2026)
The acceleration of growth during adolescence must be accompanied by the provision of adequate nutrition. It was also necessary to monitore their nutritional status to prevent nutritional problem. This was more important to do in student who enrolled in boarding schools because it tend to be lacking in proving adequate food. This research aimed to determine the relationship between energy and macronutrient adequacy and the nutritional status of students at the Salafiyah Al-Amin Islamic Boarding School, Sleman, Yogyakarta. This research was a cross-sectional research design. All of population who met inclusion and exclusion criterias were invited as respondents (40 students). The BMI/A index was used to determine nutritional status, while the level of energy and macronutrient adequacy was determined by comparing nutrient intake from three 24-hour food recalls with AKG. Data was analysed using the Pearson test. The average of energy, protein, and fat adequacy of students was insufficient, which were 73,66%, ±11,54%, 70,82%, ±8,17%, and 79,96%, ±7,66%, respectively. In the other hand, the average of carbohydrate intake was sufficient, namely 81,63%, ±3,43%. The majority of students had normal nutritional status. The Pearson test results showed a correlation between the nutritional status and the levels of energy adequacy (p=0.023; r=0.359) and fat (p=0.023; r=0.358). In the other hand, the nutritional status of students was not correlated with the level of protein adequacy (p=0.101; r=0.263) and carbohydrates (p=0.185; r=0.185). This result emphasized the importance of providing adequate food in order to maintain students' nutritional status and health.